MOBILE ASSISTED LANGUAGE LEARNING: INCREASING STUDENTS’ READING INTEREST TROUGH E-BOOK - Faradilla Fatich Narulita Mahendra (Acitya: Journal of Teaching and Education, 2020)
The purpose of this article is to review theories and previous studies about the potential offered by e-Book to increase students’ interest in reading. In Indonesian context, where English serves as a foreign language, the problem is the students tend to have low reading habits. According to PISA, by the level of literacy in Indonesia ranks the second lowest from 61 countries. Another fact shows that Indonesia is the country with the fourth largest active smartphone users in the world after China, India and America.one of the alternative ways to deal with this problem is that students must be directed to read text on the screen through online application like e-Books. This article then will discuss deeper about the theory of reading and e-Book, the reason why using e-Book as media of learning reading and how to use e-Book in reading class. Some previous research highlighting the effect of e-Book on the students’ reading interest and how e-Book can increase students’ reading interest will be the next discussion. This paper finally presents conclusion and pedagogical implication as the closing remarks.